Caffeine for the prevention of postoperative nausea and vomiting - Richard A Steinbrook; Frances Garfield; Stacey H Batista; Richard D Urman (Wolters Kluwer Medknow Publications, 2013)
Context: Postoperative nausea and vomiting (PONV) is common after ambulatory surgery performed under general anesthesia. Anecdotal evidence suggests that caffeine may be useful in preventing PONV. Aims: The aim of the study was to determine efficacy of intravenous (IV) caffeine given prior to surgery is effective prophylaxis against PONV. Settings and Design: We conducted a prospective, randomized, double-blind, placebo-controlled study. Subject and Methods: Patients at moderate or high risk of PONV were randomized to receive IV caffeine (500 mg) or saline placebo during general anesthesia; all patients received dexamethasone and dolasetron. Statistical analysis: Statistical comparisons were tested using bivariable linear and logistic regression for each outcome and then adjusted for high/low risk. Results: Nausea in the postanesthesia care unit (PACU) was more common in the caffeine (16 of 62 patients) than the placebo group (seven of 69; P = 0.02). There were no significant differences in the use of rescue antiemetics in the PACU, in the incidence of nausea or vomiting over 24 h postoperatively, nor in other outcomes (headache, fatigue, or overall satisfaction) either in the PACU or at 24 h; time-to-discharge was similar for both groups. Conclusion: Caffeine was not effective in the prevention of PONV or headache, and did not improve time-to-discharge or patient satisfaction.